أثر النمو السكاني في التركيب التعليمي للسكان في سورية خلال الفترة (1994-2010) - الرفاعي عبد الهادي; عايد محمد (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يهدف هذا البحث إلى تسليط الضوء على واقع النمو السكاني ومكوناته, إبراز الخصائص والتغيرات الحاصلة في البنية التعليمية للسكان في سورية خلال الفترة المدروسة, ومعرفة الموقع الذي يحتله السكان في سورية على درجات السلم التعليمي, وذلك من خلال تحليل النسب المئوية لكل مستوى من المستويات التعليمية. ومن أبرز النتائج التي تم الوصول إليها أنّ هناك علاقة طردية وضعيفة جداً وغير دالة إحصائياً بين تغيرات معدل النمو السكاني والتغير في التركيبة التعليمية للسكان في سورية, وبالتالي يمكن أنّ تعزى التغيرات في التركيبة التعليمية لمتغيرات أخرى غير معدل النمو السكاني, كالسياسات التعليمية, الإنفاق الحكومي على التعليم, سياسة الاستيعاب الجامعي, ...الخ. This research aims to shed light on the reality of population growth and its components and highlighting the characteristics and changes in the educational structure of the population in Syria during the period studied. This study also aims at knowing the position occupied by the population in Syria on the steps of the educational ladder, through the analysis of the percentages for each stage of educational levels. One of the most distinctive results that have been reached, that there is a direct relation yet weak and insignificant statistically between the changes of the population growth rate and those of the educational structure in Syria. Accordingly, those changes of the educational system are related to other changes than the ones of the population growth rate such as the education, government expenditure on education and higher education assimilation policies ,etc.